Biological function and molecular mechanism of piRNA in cancer - Chalbatani, Ghanbar Mahmoodi; Dana, Hassan; Memari, Feridon; Gharagozlou, Elahe; Ashjaei, Shirin; Kheirandish, Peyman; Marmari, Vahid; Mahmoudzadeh, Habibollah; Mozayani, Farnaz; Maleki, Ali Reza; Sadeghian, Ehsan; Nia, Elham Zainali; et al. (Practical laboratory medicine, 2019)
Cancer is the second leading cause of death globally. piRNAs, which are a novel type of identified small noncoding RNA (ncRNA), play a crucial role in cancer genomics. In recent years, a relatively large number of studies have demonstrated that several piRNA are aberrantly expressed in various kinds of cancers including gastric cancer, bladder cancer, breast cancer, colorectal cancer and Lung cancer and may probably serve as a novel therapeutic target and biomarker for cancer treatment. The present review summarized current advances in our knowledge of the roles of piRNAs in cancer.